Identification of Banana Morphology in Togoliua Village West Tobelo District - Kastanja, Ariance Y.; Syawal, Askia; Patty, Zeth (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research aims to determine the type and morphology of bananas in Togoliua Village, West Tobelo Sub-district, which was carried out using a survey method by taking samples from the banana population found on farmers' land and continuing with measurements and observations of each observed parameter. Data analysis was carried out descriptively and presented in the form of tables and figures. The results of identifying types of bananas in Togoliua Village, West Tobelo District found 9 types of banana plants, namely kepok bananas, raja bananas, mulu bebe bananas, Pinang bananas, goroho bananas, Manado bananas, tanduk bananas, batu bananas and mas panjang bananas. The research also noted that there are differences in morphological characters between the 9 types of banana plants, especially in the morphological characters of stems, leaves, midribs, banana flowers and fruit..